(3GdfXe GdbGfhfjI hGdGLJeGYjI hGdSjGSjI aj TQjYI MehQGHj (B/ s - (3CMeO fHjd YHO GdLdjd YeQs; (3eMehO YR GdYQH GdSbG (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI(B.s, 2017)
(3JfUH OQGSJfG Ydi MbHg gGeg ef MbH GdJGQjN GdbOje h eQMdg JTcdJ NdGdgG MVGQg YQjbg SWQJ JGQjN YXje djS HGdgjf h hVYJ gPg GdMbHg VhGHW GdcKjQ ef TFhf GdMjGg ShGA GdELJeGYjI Ch GdbGfhfjI Ch GdSjGSjI JTcdJ ef NdGdgG OhdI bhjg YGTJ eFGJ GdSfjf Ydi gPg GdGQV Jdc GdMVGQI GdJi fTCJ ai HdGO GdfgQjf Ch GdYQGb GdbOje ceG OQL Ydi JSejJgG GdeDQNjf hGdHGMKjf(B. (3h dPdc dG jLH Cf fZad Jdc GdaJQg Gdbhjg GdJi TcdJ GdcKjQ ef GdbhGfjf h GdJi CUHMJ ai Wj GdReGf eY eQhQ GdhbJ h fQHW Hjf gPg GdbhGfjf GdJi LGAJ aj TQjYI MehQGHi h eG hUd EdjfG ef bhGfjf fJOGQSgG(B. (3h CjVG dG jLH Cf fZad eG bO bjd h HMb (B" (3Cfg EPG cGfJ bhGfjf GdeLJeY GdHTQi de JYO gi ceG cGfJ aj GdeGVj, EP Cf eQLY Pdc Cf TjFkG bO JZjQ ai GdEfSGf, EP Cf GdEfSGf dG jacQ Gdjhe ceG cGf jacQ HGdCeS, h gh HMSg h EOQGcg jQfh UhH GdSeh h GdEOQGc h GdQbj h GdJbOe, h GdeLJeY GjVkG jJWhQ h jfJbd ef hVY dCNQ aj Xd eG jOhQ aj CQhbJg ef GdhGf GdacQ GdJj JSLd MVGQJg eG Hjf GdLehO h GdJWhQ h GdEROgGQs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2017.s
(3HHdjhLQGajG(B: (3UaMGJ (B241-247.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3adSaI GdbGfhf hJGQjNgs; (3GdEeHQGWhQjI GdHGHdjI GdChdis; (3MehQGHjs; (3XGgQI GdWHbjIs; (3GdWHbI GdCQSJbQGWjIs; (3WHbI GdehTcjfhs; (3WHbI GdGQbGAs; (3GdRhGL aj TQjYI MehQGHjs; (3GdeQCI aj YgO MehQGHjs; (3OhjdGJ GdeOfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2017